A SYSTEMATIC LITERATURE REVIEW ON THE RELATIONSHIP BETWEEN INTEGRATED REPORTING AND MARKET VALUATION - Said, Roshima; Wan Ismail, Wan Adibah; Kamarudin, Khairul Anuar; Che Adenan, Nur Zharifah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This study analyzes the existing literature on the adoption of integrated reporting and its implications for firms’ market value. Guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, a systematic literature review was conducted using the Web of Science and Scopus databases, supplemented by additional relevant sources. The analysis identified two key themes related to the implementation of integrated reporting in voluntary and mandatory settings. The findings indicate mixed results regarding the relationship between integrated reporting and market value in voluntary settings. In contrast, almost all studies demonstrated a positive association between integrated reporting and market valuation in mandatory settings. The review synthesizes existing evidence to provide broader insights into the relationship between integrated reporting and market valuation.The findings offer valuable insights for researchers, practitioners, and regulators involved in the development and implementation of integrated reporting policies.